Prosopanche: a remarkable genus of parasitic plants - Hatt, SA; Cameron, DD; Grace, OM; Rocamundi, N; Cocucci, AA; Martel, C; Thorogood, CJ (Wiley, 2022)
Prosopanche is a poorly known genus of parasitic plants from South and Central America. Growing almost entirely underground with a complete lack of leaves, plants of Prosopanche bear more resemblance to fungi than plants and have many remarkable aspects to their life history and ecology that require further investigation. Here, we provide an up-to-date revision of the current state of understanding of Prosopanche, including taxonomy, biogeography, plant-pollinator ecology and host-parasite interactions. We discuss the untapped research potential of this group of plants and recommend the Prosopanche as an ideal candidate for exploring the evolutionary origins of parasitism among flowering plants.